The effect of price-earnings ratio and price-to-book ratio on stock prices in the banking sector on the indonesia stock exchange for the period 2023–2025 - Genta Arya Pradana; siti nurhazizah; Mangasi Sinurat; Willy Cahyadi (Jurnal Mantik, 2026)
This study aims to analyze the influence of corporate fundamentals, proxied by the Price Earning Ratio (PER) and Price to Book Value (PBV), on stock prices in the banking sector listed on the Indonesia Stock Exchange (IDX) for the 2023–2025 period. The research method used is quantitative with a purposive sampling approach, resulting in a sample of 12 banks with a total of 36 panel data observations. Data analysis was performed using panel data regression via Eviews 12 software. Simultaneous testing (F-test) results show that PER and PBV variables collectively have a significant impact on stock prices. Partially (t-test), it was found that PBV has a dominant positive and significant influence, while PER exhibits a significant negative influence on stock prices. The Adjusted R-squared value of 99.32% indicates that stock price variations in the banking sector are almost entirely explained by these two independent variables. These findings suggest that investors in the banking sector prioritize intrinsic equity value (net asset value) as an indicator of investment security over mere earnings multiples expectations. Theoretically, this study reinforces the Signaling Theory by demonstrating that in the banking industry, asset-based information (PBV) provides a more reliable signal of long-term solvency than earnings volatility. However, this study is limited by its specific focus on the KOMPAS 100 index and a relatively short observation period, which may affect the generalizability of the results to smaller or digital-only banks. This study recommends that investors utilize fundamental valuation ratios, particularly PBV, as primary instruments for investment decision-making in the banking sector